Prevalence of gentle herpes simplex type 2 in Babylon province for last 3 years: A retrospective descriptive data analysis - Ammar Abbas Shalan; Nada Khazal K. Hindi; Mohammed Malih Radhi; Zainab Adil Ghani Chabuck (Medical Journal of Babylon)
Abstract Background: Herpes simplex virus type 2 (HSV-2) infection stands as a prevalent sexually transmitted disease with global ramifications. Understanding its prevalence across different age groups and genders is crucial for an effective control and management. Objectives: This study is aimed to retrospectively investigate the prevalence of HSV-2 infection based on age and gender categories. Materials and Methods: A descriptive analytical design was conducted for the periods of April 28 and May 23, 2023. Examination of medical records unveiled a total of 91 confirmed positive cases. Data collection encompassed hospitals, private clinics, and health institutions. A descriptive and inferential statistical analyses were done to glean meaningful insights. Results: The prevalence of HSV-2 infection exhibited a marked gender discrepancy, with females accounting for the highest proportion (60.4%). Notably, individuals aged 15-50 exhibited a substantial prevalence rate of 52.7%. The findings further illuminated a progressive rise in mild herpes prevalence with advancing age. The infection’s prevalence trajectory showed a notable shift over time, with the lowest rate recorded in 2020, gradually ascending to its zenith in 2022. Statistical assessments unveiled significant disparities in HSV-2 prevalence across age and gender strata. Older individuals displayed higher prevalence (p = 0.002), while a profound gender influence was evident, with females displaying a significantly greater prevalence (p = 0.000). Conclusions: With the infection’s persistent nature and the availability of serologic testing, gauging HSV-2 frequency becomes a straightforward task. Despite potential limitations stemming from incomplete data, the study unequivocally underscores the widespread nature of HSV-2 infection. The insights gleaned from this study serve as a pivotal foundation for formulating targeted interventions and preventive strategies on a global scale.